PURIFICATION OF BETA-GLUCOSIDASE FROM APRICOT SEEDS TO REDUCE THE TOTAL VICINE –CONVICINE CONTENT IN FABA BEANS (VICIA FABA L.) - K. A. Shaker; Marie K. Walsh; H. K. Ali; J. M. Nasser (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
This research was aimed to purified beta-glucosidase from apricot seeds using ammonium sulfate precipitation, followed by gel filtration chromatography, then ion exchange chromatography. Ion exchange chromatography resulted in the enzyme sample with a specific activity of 41.3 U/mg with a purification fold of 15 and a yield of 30.3%. The apricot beta-glucosidase had an optimum pH of 4 with good stability between pH 3 and 6. The optimum temperature was 60°C and there was good stability between 5 and 40°C. Faba beans treated at pH 5.5 containing beta-glucosidase showed higher total vicine removal than with only water at pH 5.5 after 4 h. Additionally, treatment at 40°C showed higher total vicine removal that treatments at 25°C. However, treating faba beans at pH 5.5 with and without beta-glucosidase resulted in a lower total vicine content for the enzyme treatment before cooking but the total vicine content after cooking was the same for the water treated compared to the enzyme treated. As an industrial by-product, apricot seeds are a rich source of beta-glucosidase that may be used to treat faba beans to increase their nutritional composition.